English Task To Develop The Students' Communicative Competence: A Study Of Edukatif Work Book For Junior High School Students - Rohmawati, Dyah (2012)
This research is mainly intended to find out the extent tasks in Edukatif work books are designed to develop the students' communicative competence. The objective of this research is to explain what extent the tasks in Edukatif work books are designed to develop students' discourse competence, linguistic competence, actional competence, sociolinguistic competence, and strategic competence. This research is qualitative research which involves content analysis approach. The object of this research is English work book named Edukatif that published by Akik Pusaka Sragen. The writer analyzes the work book of eight grade students including the work book that used in the first and second semester. In collecting the data, the writer uses documentation method. The data analyze used the theory of Hiberman and Miles which involves data reduction, data display and verification. The findings show that among the five competences and its components of communicative competence, some components are not developed in both work books. Both Edukatif work book one and two can develop all components of discourse competence. But the tasks do not develop one aspect in linguistic competence that is phonology. Moreover, work book one and two can develop most component of actional competence, except speech act (in work book one) and problem key area (in work book two). Some tasks in both work books also develop two components- among four components-of sociolinguistic competence, except cultural and non-verbal communicative factor. Latter, the work book only develop one component-among five components- of strategic competence that is time and gaining strategy. So, considering the result above, the writer can conclude that the tasks in both Edukatif work books are not sufficient to develop the students' communicative competence, especially in developing sociolinguistic and strategic competence.